Determination of cassava root yield and aboveground biomass by crop cut at plot level - Hauser, Stefan (2023)
Cassava is usually grown for its starchy storage roots; however, in many sub-Saharan African countries, cassava leaves are harvested and consumed as a vegetable. This SOP deals with the determination of storage root yield and aboveground biomass. Cassava storage roots are commonly marketed as fresh roots and most yield data in the literature are expressed as fresh root yield, although this is in most cases not explicitly stated. This SOP provides guidelines to determine the storage root fresh and dry matter yields and the fresh and dry edible portion of the storage roots. Cassava is planted from stem cuttings and thus the amount or length of marketable planting material is of commercial interest. This SOP provides guidelines to determine the mass and the length of planting material. For agronomic and physiological purposes, the total plant biomass may be required. This SOP provides guidelines on how to determine the mass and the dry matter content of all aboveground plant material.